Estudo da viabilidade da produção de briquetes e seus possíveis impactos sobre o meio ambiente e o mercado de trabalho da região do baixo-Açu, RN - Tavares, Marilia Amaral de Moura Estevão (2013)
Ninety-eight percent of Rio Grande do Norte territory are included in the so-called Desertification Susceptible Areas in Brazil (ASD). In Lower-Açu, native forest s systematic and uncritical deforestation in order to attend ceramist polo and small local industries needs has intensified the framework of environmental devastation, now considered serious by the Ministry of Environment. The field survey designed to measure the consumption of firewood and charcoal in the region revealed that the demand for these two fuels is eight times greater than the supply, according to IBGE data on extractive production of the nine counties that comprise the region. This study examined the viability of implanting an embryo of briquettes Local Productive Arrangement production (ecological firewood) on Ipanguaçu Campus of The Federal Institute of Education, Science and Technology of Rio Grande do Norte in order to contribute in the development of public policies that promote the recovery of deforested areas and alleviating human pressure on Caatinga. The briquettes would be produced to replace firewood and charcoal as fuel, especially in the ceramic industries polo of that region. The main raw material are the waste from the carnauba wax production, and they will be enough to ensure the production of five plants with a production capacity of 4800 ton of briquettes per year each. Besides carnauba straw, elephant grass will be used to compose 20% of briquettes blend. Estimative of biofactory s maintenance costs were made having as parameter a similar industrial plant data, located in Paraná. These data were summarized in spreadsheets Make Money software, used in economic viability evaluations based on sealers such as Net Present Value (NPV), Payback and Internal Rate of Return (IRR). The results confirmed that the project is viable. Besides the analysis for the real factory, under construction on IFRN campus, this work has produced two other products: the economic viability analysis of a more commercial factory, with lower deployment costs, and NPV estimation models, Payback and TIR in 5, 10, 15 and 20 years, for any values of biomass buying and briquette selling, if under the same conditions of the analyzed plants. The objective was to provide a tool for analyzing economic and financial viability for future similar plants that might be settled in the region, generating jobs and income for the population and allowing the recovery of native forest.